2002
DOI: 10.1152/jn.00491.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Representation of Auditory Space: Information-Bearing Features of Spike Patterns

Abstract: Furukawa, Shigeto and John C. Middlebrooks. Cortical representation of auditory space: information-bearing features of spike patterns. J Neurophysiol 87: 1749 -1762, 2002; 10.1152/jn.00491.2001. Previous studies have demonstrated that the spike patterns of cortical neurons vary systematically as a function of sound-source location such that the response of a single neuron can signal the location of a sound source throughout 360°of azimuth. The present study examined specific features of spike patterns that mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
147
2
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 38 publications
(44 reference statements)
11
147
2
5
Order By: Relevance
“…Indeed, previous studies demonstrating an increase in the reliability of cortical neural responses in response to dynamic stimuli (de Mainen and Sejnowski 1995) are consistent with this idea because an increase in reliability of cortical responses would be expected to improve discrimination. Previous studies in auditory cortex have demonstrated the high degree of temporal precision in auditory cortical responses (DeWeese et al 2003;Elhilali et al 2004;Heil 1997;Heil and Irvine 1997) and the contribution of spike timing in the information transmitted by cortical neurons about time-varying stimuli (Lu and Wang 2004;Wright et al 2002) and sound location (Furukawa and Middlebrooks 2002). This study demonstrates the significant contribution of spike timing to the discrimination of complex sounds by single cortical neurons.…”
Section: Spike Timing Versus Firing Rates In Cortical Discriminationsupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, previous studies demonstrating an increase in the reliability of cortical neural responses in response to dynamic stimuli (de Mainen and Sejnowski 1995) are consistent with this idea because an increase in reliability of cortical responses would be expected to improve discrimination. Previous studies in auditory cortex have demonstrated the high degree of temporal precision in auditory cortical responses (DeWeese et al 2003;Elhilali et al 2004;Heil 1997;Heil and Irvine 1997) and the contribution of spike timing in the information transmitted by cortical neurons about time-varying stimuli (Lu and Wang 2004;Wright et al 2002) and sound location (Furukawa and Middlebrooks 2002). This study demonstrates the significant contribution of spike timing to the discrimination of complex sounds by single cortical neurons.…”
Section: Spike Timing Versus Firing Rates In Cortical Discriminationsupporting
confidence: 60%
“…Surprisingly, the optimal temporal resolution we found at the cortical level was comparable to the optimal temporal resolution at the sensory periphery. Previous studies in auditory cortex have demonstrated the high degree of temporal precision in auditory cortical responses (DeWeese et al 2003;Elhilali et al 2004;Heil 1997;Heil and Irvine 1997), and the contribution of spike timing in the information transmitted by cortical neurons about time-varying stimuli (Lu and Wang 2004;) and sound location (Furukawa and Middlebrooks 2002). It is important to emphasize that the notion of the optimal temporal resolution for a detection or discrimination task is distinct from the temporal precision of neural responses, and these two quantities need not be the same for a neural code (Chichilnisky and Kalmar 2003).…”
Section: Optimal Temporal Resolution For Discriminationmentioning
confidence: 99%
“…Although noted, the impact of such heterogeneity on multisensory interactions has not been systematically investigated. Multisensory neurons in the cat AES provide an excellent substrate within which to investigate this issue, both because their receptive fields are quite large and because it has been suggested that these neurons encode spatial information via differential responses as a function of stimulus location (Benedek et al 2004;Eordegh et al 2005;Furukawa and Middlebrooks 2002;Middlebrooks et al 1984Middlebrooks et al , 1998Nagy et al 2003a,b;Xu et al 1999). Consequently, in the current study we set out to begin to characterize the spatial heterogeneity of receptive fields in multisensory AES neurons and, more important, to examine how this architecture contributes to the multisensory interactions that characterize these neurons.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies quantifying first-spike latency information assume that the brain has an independent reference for stimulus onset from which to extract latency. In the majority of situations, this independent onset reference does not exist; the need for a timing reference has caused some to question the ultimate feasibility of first-spike latency codes (8).A number of authors have suggested possible alternative latency measures (1,3,5,6), but few have actually compared the information contained in different onset references. Stecker and Middlebrooks (9) computed the information contained in the relative spike timing of pairs of simultaneously recorded neurons in auditory cortex, and Furukawa et al (10) compared the median errors from neural-network estimates of location with similar data.…”
mentioning
confidence: 99%
“…A number of authors have suggested possible alternative latency measures (1,3,5,6), but few have actually compared the information contained in different onset references. Stecker and Middlebrooks (9) computed the information contained in the relative spike timing of pairs of simultaneously recorded neurons in auditory cortex, and Furukawa et al (10) compared the median errors from neural-network estimates of location with similar data.…”
mentioning
confidence: 99%